PENGARUH KEBIJAKAN HUTANG DAN DIVIDEN TERHADAP NILAI PERUSAHAAN DISEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amrizal Salida; Kurniawan; Usman (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study has a goal, which is to see how influential a company's debt policy problems and also the distribution of dividends for each company are on the value of the company itself. The companies that are the object of this research are companies listed on the Indonesian stock exchange, while the subject of the company is a company engaged in the telecommunications sector. This study uses inferential statistical data analysis with multiple regression approach. The test is carried out to strengthen that the data used is objective, then the data will be tested for F and T tests, after that the data is then tested again using the coefficient of determination test using the help of the SPSS application. To determine the sample in this study, the saturated sample method was used, the results obtained were 30 samples consisting of 6 companies and each company used financial statement data for the past 5 years. The data obtained in this study were sourced from the Indonesian stock exchange. Broadly speaking, the results of the F and T tests show that the problem of debt policy and dividend distribution does not have a positive and significant effect on the value of a company.